The changing political trends in erstwhile FATA: a study of the last three elections. (December 2021) - Ahmed, Raja Qaiser; Ishaq, Mohammad; Shoaib, Muhammad
This study investigates the changing political trends in erstwhile Federally Administered Tribal Areas of Pakistan. Analysis of the last three elections (2008, 2013, 2018) shows a substantial change in the region. The tribal structure, local traditions, power arrangement and electoral practices have changed significantly over a decade. The extension of the Political Parties Order to the region and its merger with Khyber Pakhtunkhwa stimulated political activities in the area that increased the political awareness of tribal people. The results of the 2013 and 2018 elections highlight the changes. Electoral activities, women participation and voter turnout increased with every election. Tribal youth joined existing political forums to demand their democratic rights. A significant percentage of the young, educated Pashtuns joined the Pashtun Tahafuz Movement in its demand for improved governance.